Mapping elementary school students' creativity in science process skills of life aspects viewed from their divergent thinking patterns - Subali, Bambang; Paidi, Paidi; Mariyam, Siti (REID (Research and Evaluation in Education), 2017)
The purpose of this study was to map elementary school students' creativity in science process skills (SPS) of life aspects in science subjects viewed from their divergent thinking patterns using written tests whose items were fitted with Partial Credit Model (PCM). The measurement used a test validated using the IRT approach published in JEE journal in 2015. The trials employed four sets of test, each comprising 20 items completed with anchor items which were fitted referring to PCM. The measurements were performed with larger scale on 14 regional technical implementation unit (RTIU) in Yogyakarta Special Province in five regencies/cities to students of grades IV, V, and VI. The findings showed that the higher the grade level, the higher of the testees' scores would be. There were some testees who did not have divergent thinking ability and they obtained a score of 0 The divergent thinking ability of the students was not related to the regency/city where an RTIU was located.